1991
DOI: 10.1002/jcu.1870190204
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal and transabdominal ultrasonography of the uterine cervix during pregnancy

Abstract: Transvaginal and transabdominal ultrasound evaluation of the uterine cervix were compared in a study of 186 pregnant women. An empty bladder made transabdominal ultrasound measurement of the cervix more difficult, while bladder filling resulted in significant lengthening of the transabdominal cervical measurement. In contrast, transvaginal ultrasound cervical measurement was possible in all but 1 patient. Normal transvaginal ultrasound cervical measurements were significantly shorter on average than transabdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
15

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 12 publications
7
81
0
15
Order By: Relevance
“…Results of other studies are more variable: some found that cervical length did not change during pregnancy 12 , others found a continuous decrease from 10 to 40 weeks 13 or from 17 to 37 weeks 20 , while others still 14 reported that the cervix became longer between 8 and 25 weeks and then shortened. In most studies cervical length did not differ between nulliparous and parous women 13,14,20,28,29 , however in some the cervix was longer in parous women 17,18 . The discrepant results may be explained by differences in measurement technique, study design, the period in gestation studied, the statistical methods used, and the interpretation of the results.…”
Section: Discussionmentioning
confidence: 88%
“…Results of other studies are more variable: some found that cervical length did not change during pregnancy 12 , others found a continuous decrease from 10 to 40 weeks 13 or from 17 to 37 weeks 20 , while others still 14 reported that the cervix became longer between 8 and 25 weeks and then shortened. In most studies cervical length did not differ between nulliparous and parous women 13,14,20,28,29 , however in some the cervix was longer in parous women 17,18 . The discrepant results may be explained by differences in measurement technique, study design, the period in gestation studied, the statistical methods used, and the interpretation of the results.…”
Section: Discussionmentioning
confidence: 88%
“…Cervical assessment can also be carried out by transabdominal and transperineal sonography and these alternative routes may be more acceptable to some women. However, transabdominal sonography fails to visualize the cervix in a high proportion of cases and in particular those with a short cervix [3][4][5][6] . Furthermore, successful visualization by transabdominal sonography requires a full bladder which falsely increases cervical length.…”
Section: Introductionmentioning
confidence: 99%
“…The probable explanation of the TAS measurement being longer than that of the TVS lies in the fact that bladder filling causes an increase in cervical length. A number of studies have established the fact that, although a variable degree of bladder filling has an advantage of improving the visualisation of the cervix in pregnant patients by TAS, it causes artificial lengthening of the cervix (7,9,11,12). This may be explained by the fact that the endocervical mucosa cannot be clearly recognised by TAS (in contrast with TVS where the endocervical mucosa can be recognised clearly) and the internal os is falsely thought to be at a higher level than it actually is in reality.…”
Section: Discussionmentioning
confidence: 99%